Variation of dystopian control systems in selected novels by Huxley, Vonnegut, and Delillo - Khorzughi, Ruzbeh Babaee (2014)
During a time of emergence of new technologies, six outstanding pieces of dystopian fiction appeared from three unconventional writers: Aldous Huxley’s Brave New World, and Ape and Essence; Kurt Vonnegut’s Player Piano, and Slaughterhouse-Five; and Don DeLillo’s White Noise, and Cosmopolis. The present thesis investigates the dystopian essence of these narratives from the perspectives of technological advances and human manipulation. It is an exploration of the ways in which these texts represent the formation of dystopia and the manipulation of human being through technological developments in cyborg culture from the early twentieth century to the early twenty-first century. My reading of dystopia is an investigation of well established critical materials by such scholars as Tom Moylan, Chad Walsh, Mark R. Hillegas, M. Keith Booker, and Erika Gottlieb among some others. Throughout the analysis, I highlight human manipulation via technology in these six dystopias through the theories of Donna Haraway, Michele Foucault, Katherine Hayles, Dani Cavallaro, Norbert Wiener, Gilles Deleuze and Felix Guattari. This study examines chronologically the idea of human manipulation in cyborg culture that promised us utopia through a combination of the human and the nonhuman, or humans and machines. But, the utopian desires of cyborg culture have led to dystopian societies in which human dignity is devalued. In this study, I consider human manipulation through biopower (disciplinary systems), cybernetics, and cyberspace as postmodern control systems that have trapped human beings in technological, mechanized, and simulated environments. I also attempt to show the variations in technological dystopian societies in selected dystopian narratives. I examine Huxley’s selected dystopian novels via the concept of biopower that manipulates people and turns them into docile bodies with disciplined minds. I investigate Huxley’s Brave New World and Ape and Essence to show how mind manipulation will guarantee and reinforce body manipulation. For Huxley, in order to convert human beings into docile productive bodies, their minds must believe in the righteousness of the actions of the body. Moreover, I propose cybernetics as a significant control system while investigating and understanding dystopian fiction. In this study, I examine the ways in which individuals in the dystopian societies of Player Piano and Slaughterhouse-Five are manipulated and exploited via cybernetics in the mid twentieth century. Cybernetics marginalizes human beings and turns them into intelligent machines and thoughtless consumer bodies. Cybernetics imposes a quite different kind of control over individuals. It is not a form of control that directly confines freedom of action; instead it is a subtle electronic control that affects human mind. Furthermore, I suggest that DeLillo’s White Noise and Comopolis are dystopian narratives about human body control in cyberspace in the late twentieth and early twenty-first centuries. DeLillo demonstrates that the visible world is generated via a hidden informational world. He also suggests this invisible informational world is influenced by the visible world. Therefore, technology can manipulate the body based on particular cultural requirements. DeLillo shows that cyberspace creates simulation and hyperreality in order to entrap the human body. For DeLillo, in cyberspace people become disembodied and enmeshed into pattern, access, megalomania and paranoid schizophrenia.